Mass Housing Neighbourhoods and Urban Commons: Values-based Governance and Intervention Framework for New Belgrade Blocks - Dragutinovic, Anica (A+BE | Architecture and the Built Environment, 2023)
The neglect of significance, deterioration and consequent devaluation of the post-war mass housing neighbourhoods are major challenges, both in the field of heritage conservation and management and in urban planning and design. The reasons for their deterioration are different, and interlinked with the socio-cultural discourse, as well as the spatial characteristics of these neighbourhoods. This doctoral research addresses the challenges of those neighbourhoods, focusing on New Belgrade Blocks, as one of the largest modernist post-war mass housing areas in Europe. The case is particularly important for the discourse on mass housing and ‘ordinary’ heritage management, as it encapsulates concepts, policies and practices developed in Yugoslavia, which are relevant to the contemporary discussions on community-driven approaches for urban planning and governance and participation in heritage studies. The doctoral thesis presents this legacy and reveals causalities and relations of spatial and socio-political aspects, policies, but also planning and design principles. Furthermore, it empirically studies and evaluates the blocks in the contemporary context, with the society (involving citizens), and within the current legal and organisational conditions. Eventually, it develops a framework for enhancement of the blocks, addressing the current and future societal and users’ needs, while preserving the identity and values of the blocks. The doctoral thesis provides different findings and perspectives, contributing to the current knowledge on integrated conservation, urban planning and governance of urban heritage, and in particular mass housing neighbourhoods. It shows co- dependence of those fields and offers an integrative and cross-disciplinary approach.